Modification of eggshell and seashell wastes as catalyst in biodiesel production / Mohd Zaki Sukor ...[et al.] - Sukor, Mohd Zaki; Sa'ari, Mohd Syahir; Jasman, Norhanida; Haidzir, Alif Affandi
In recent years, the used of catalyst had become a norm to speed up the production of biodiesel from vegetable oils. In this work, egg-seashell wastes which are rich in calcium oxide (CaO) are used as catalyst to accelerate the production of biodiesel from palm oil. The catalysts were prepared via calcination method at 400°C, 500°C, 700°C, 900°C and 1000°C for 1.5 h, 2.5 h and 3.5 h for each consecutive temperatures. The experimental parameters were reaction time, reaction temperature, methanol/oil molar ratio and catalyst loading on the transesterification for the production of biodiesel has been also consider to get higher yield. All the parameters were proceeded by 5 wt% of catalyst, methanol to oil ratio was 2: 1 and a reaction temperature of 65° C with reaction time of 1 h. The catalyst performance is measured according to their conversion percentage. Under the possible optimum reaction conditions, the highest conversion achieved was 85.7%.